2015
DOI: 10.3109/02699052.2014.995226
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life for individuals with a vestibular impairment following an acquired brain injury (ABI); the clients’ perspective

Abstract: Individuals who suffer a brain injury and experience vestibular symptoms as part of their overall presentation are not diagnosed in a timely manner, with individuals, their families, associates and even health professionals feeling uncertain of the legitimacy of their reported symptoms. It is important that all patients who experience an acquired brain injury are screened for vestibular impairment and, if necessary, receive vestibular rehabilitation including explanation and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
2
6
0
2
Order By: Relevance
“…There appears to be a combination of symptoms that this population experiences including environmental sensitivity, cognitive and communication difficulties, impaired balance, pain, fatigue, and difficult emotional responses. These challenges are consistent with the literature (Hellerstein & Scheiman, 2011;Killington et al, 2015;Suter et al, 2011). All these challenges together and in isolation interfere with participation in everyday activities and social roles.…”
Section: Complex Situation: Not Just Visionsupporting
confidence: 92%
“…There appears to be a combination of symptoms that this population experiences including environmental sensitivity, cognitive and communication difficulties, impaired balance, pain, fatigue, and difficult emotional responses. These challenges are consistent with the literature (Hellerstein & Scheiman, 2011;Killington et al, 2015;Suter et al, 2011). All these challenges together and in isolation interfere with participation in everyday activities and social roles.…”
Section: Complex Situation: Not Just Visionsupporting
confidence: 92%
“…Several large population-based studies have previously observed an association between vestibular loss and poorer health-related quality of life using standardized quality-of-life questionnaires [25, 26]. A few prior studies have taken a qualitative approach, specifically in patients with traumatic brain injury with resulting vestibular loss, a group of patients undergoing vestibular rehabilitation, and in individuals with Meniere's disease [2729]. In addition, Yardley has well documented the lived experience of a wide range of individuals suffering from dizziness and vertigo [30].…”
Section: Discussionmentioning
confidence: 99%
“…Les déficits visuels et le diagnostic de TCC-MG sont intimement liés à plusieurs autres dysfonctions que la vision. Ils ont des effets souvent durables et graves sur les tâches motrices, sociales, cognitives, communicationnelles, et émotionnelles (Ciuffreda et al, 2007; Greenwald et al, 2012; Killington et al, 2015; Lew et al, 2009; McDonnall et al, 2020; Wilson et al, 2017); et sur la plupart des autres aspects de la vie, à travers une cascade d’effets indirects. Ainsi, le diagnostic de TCC-MG représente une grande menace pour la Qualité de Vie (QdV; Cuthbert et al, 2015; Seibert et al, 2002; Takada et al, 2016).…”
Section: Traumatisme Craniocérébral Et Qualité De Vieunclassified